2020
DOI: 10.1038/s41598-020-67288-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Concentration is Associated with the Expression Level of Folate Receptor 3

Abstract: folic acid and folate receptors (foLRs) play an important role in the downregulation of homocysteine (Hcy), a risk factor of Alzheimer's disease, thrombosis, neuropsychiatric illness and fractures. While several studies have reported that FOLR1 and FOLR2 import folic acid into cells, the role of FOLR3 remains unknown. In this study, we evaluated the impact of FOLR3 on the metabolism of Hcy alongside its protective effect against homocysteine-induced neurotoxicity. To reveal the role of FOLR3, we constructed FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
(23 reference statements)
0
18
0
2
Order By: Relevance
“…HCys serum concentrations beyond 15 µmoL/L (≈2030 ng/mL) were considered high and referred to as hyperhomocysteinemia [ 74 ]. By feeding a diet deficient in vitamin B6, B12 and folate, we induced elevated levels of HCys beyond 15 µmoL/L and therefore, a hyperhomocysteinemic state in our mice.…”
Section: Discussionmentioning
confidence: 99%
“…HCys serum concentrations beyond 15 µmoL/L (≈2030 ng/mL) were considered high and referred to as hyperhomocysteinemia [ 74 ]. By feeding a diet deficient in vitamin B6, B12 and folate, we induced elevated levels of HCys beyond 15 µmoL/L and therefore, a hyperhomocysteinemic state in our mice.…”
Section: Discussionmentioning
confidence: 99%
“…1 Hcy metabolism. Abbreviations: blue-colored words, enzymes; green-colored words, cofactors (HHcy) [9]. Furthermore, the range of Hcy between 16 and 30 μmol/L is classified as moderate, 31-100 μmol/L as intermediate, and above 100 μmol/L as severe HHcy [6].…”
Section: Physiologic Hcy Levels and Severity Of Deviations: What Is The Most Optimal Hcy Concentration In Blood?mentioning
confidence: 99%
“…Several possible explanations have been proposed to offer some mechanistic insights. Hyperhomocysteinemia has been proposed as being part of the pathophysiology of cardiovascular disease due to its various biological effects, such as vascular damage, oxidative stress-induced DNA damage [ 32 ], neuronal apoptosis [ 33 ], cell cytotoxicity [ 34 ], and endothelial nitric oxide production [ 35 ]. Homocysteine acts as a methyl donor when it is converted to S-adenosyl-methionine, and a recent study demonstrated an association between the Hcy and DNA methylation in cardiovascular disease and dementia [ 36 , 37 ] with MTHFR C677T polymorphism, which suggests that Hcy also might play a role in the pathogenesis of those diseases via alterations in DNA methylation.…”
Section: Discussionmentioning
confidence: 99%